As boas práticas da LGPD como instrumento institucional de confiança organizacional - Czeder, Miguel de Paula (Universidade do Vale do Rio dos Sinos, 2022)
In what condition can university students who, even approved, do not enroll, leave their personal data being processed by UNIRV for the purposes of targeted advertising? It is intended to demonstrate that UNIRV, operating in the context of the 4th Industrial Revolution, must assume the responsibilities of self-governance, conforming the principles of SOCINFO with the LGPD dictates when processing the personal data of students taking entrance exams as a way of adding institutional trust. The methodology used is deductive, starting from general concepts and categories for the specific treatment of the research object, facing the problem and confirming or not the hypothesis, based on the pragmatic-systemic approach. The research techniques are composed by the bibliographical revision, national and foreign, as well as, collection of institutional data and protected documents to the qualitative theoretical analysis. The religion of the research lies in the fact that society experiences disruptions in all its dimensions due to the technologies of the 4th Industrial Revolution, which is marked by the digitization and automation of relations between society and organizations, which challenges the paradigms of regulation traditional and requires agents to self-regulate in order to increase institutional trust. The research covers the following specific objectives: (i) understanding the object from the historical context of the formation of the University in Brazil until the present day, when such organizations have in new technologies their development environment; (ii) investigate the problem between the need for marketing aimed at UniRV students and data processing, as well as the paradox between market and value; and, (iii) present the Digital Governance 4.0 applied through a Practical Guide for the elaboration of the term of consent for the collection of personal data on the registration site for the UNIRV entrance exam. It was concluded that organizations need to understand the importance of self-regulation, especially those that process personal data and, based on this finding, act proactively to integrate LGPD best practices with the principles established by SOCINFO, an attitude that not only mitigates the risks of processing personal data, but also adds institutional trust to the organization's image.
Keywords: Tratamento de dados; LGPD; SOCINFO; Confiança institucional; Governança; Data processing; Institutional trust; Governance; ACCNPQ::Ciências Sociais Aplicadas::Direito